Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1093/ve/veac013
|View full text |Cite
|
Sign up to set email alerts
|

Effects of host and pathogenicity on mutation rates in avian influenza A viruses

Abstract: Mutation is the primary determinant of genetic diversity in influenza viruses. The rate of mutation, measured in an absolute time-scale, is likely to be dependent on the rate of errors in copying RNA sequences per replication and the number of replications per unit time. Conditions for viral replication are probably different among host taxa, potentially generating the host-specificity of the viral mutation rate, and possibly between highly and low pathogenic viruses. This study investigated whether mutation r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 50 publications
0
6
0
Order By: Relevance
“…The key human-adapted amino acid substitutions of PB2 protein (PDB: 6QPF) [34] screened by Flu-CNN, visualized by Visual Molecular Dynamics (VMD) [35, 36]. The selected amino acid substitutions are denoted in blue and yellow.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The key human-adapted amino acid substitutions of PB2 protein (PDB: 6QPF) [34] screened by Flu-CNN, visualized by Visual Molecular Dynamics (VMD) [35, 36]. The selected amino acid substitutions are denoted in blue and yellow.…”
Section: Resultsmentioning
confidence: 99%
“…While identifying human-adapted amino acid phenotypes, we take the PB2 protein as a major example, because it is indispensable to virus replication and is a pivotal determinant of host range [33]. Researchers have discovered that distinct PB2 proteins affect viral growth performance, pathogenicity, and infection range [34][35][36]. Moreover, PB2 proteins are implicated in signaling pathways that follow viral infection, including blocking JAK1/STAT signaling via targeting JAK1 for degradation through proteasomal mechanisms, indicating that the PB2 protein is essential in regulating the interaction between virus and host [37].…”
Section: Discussionmentioning
confidence: 99%
“…However, due to territorial expansion, lifestyle, and international exposure, it is exceedingly difficult to find a single sub‐lineage that is unique to one country. However, the geographical origin and the local distribution of a sub‐lineage should be studied further because it may be related to a variety of factors including the genotypic characteristics of the community 29,30 . The distribution of the B.1 sub‐lineages could also be related to other factors such as mode of transmission, infection with STDs, or the patient's sex, as it has been observed that the current outbreak of 2022, unlike previous ones, is more dispersed among immunocompromised people with a preexposure/exposure to HIV, homosexual people, and through sexual contact 31–33 …”
Section: Discussionmentioning
confidence: 99%
“…None of the unique mutations identified in the HA, M1 and PA proteins of the coastal seabird viruses are known to be associated with any specific phenotype in functional studies, for example enhanced replication or virulence (Suttie et al., 2019 ), but they may represent viral adaptation to the marine hosts. Alternatively, they reflect new sub‐lineages that were emerging, and in fact shorebirds have been found to support higher viral mutation rates than wild ducks (Kim et al., 2022 ). The SA coastal seabird epidemic appeared to end by May 2018 with no further mortalities reported, but there was no ongoing active sampling of coastal seabirds due to a lack of resources.…”
Section: Discussionmentioning
confidence: 99%